Lock-in thermography for analyzing solar cells and failure analysis in other electronic components. Issue 3 (2nd October 2019) - Breitenstein, Otwin; Sturm, Steffen
ABSTRACT: Lock-in thermography (LIT) is a dynamic variant of infrared thermography, where local heat sources are periodically pulsed and amplitude and phase images of the surface temperature modulation are obtained. If used in electronic device testing, this method enables the localization of very weak local heat sources below the surface. This contribution reviews the basics and application of LIT for local efficiency analysis of solar cells and for failure analysis in other electronic components like bare and encapsulated integrated circuits. In both application fields LIT has established as a reliable and easy-to-use standard method for failure analysis.